Artificial Photosynthesis: Shifting the Sun: Solar Spectral Conversion and Extrinsic Sensitization in Natural and Artificial Photosynthesis (Adv. Sci. 12/2015). Issue 12 (December 2015) - Wondraczek, Lothar; Tyystjärvi, Esa; Méndez‐Ramos, Jorge; Müller, Frank A.; Zhang, Qinyuan
Abstract : In solar energy harvesting, large parts of the solar spectrum do not contribute to the harvesting scheme. In article 1500218, L. Wondraczek and co‐workers discuss the application of solar spectral conversion in the emerging context of photochemical energy harvesting through natural or artificial photosynthesis, arguing how such extrinsic sensitization can and cannot be employed to increase the efficiency of a photosynthetic machinery.